1e Exposition Groupe 90. (Paris : Galerie Marcel-Lenoir - Claude Namy, 1985)
Charlin, Gérard ; Fachard, Robert ; Galichet, Edith ; Hess, Esther ; Kadar, Joseph ; van Lamsweerde, Inez ; Mark, Anna ; Mohr, Dietrich ; Nagy, Paul ; Papp, Tibor ; Patkai, Ervin ; Roman, Victor ; Segovia ; Subira-Puig, José ; Tavès, Alain
biog., tent., bibliog. per kunstenaar [1 p.]
1e Exposition Groupe 90, Galerie Marcel-Lenoir - Claude Namy, Paris, 9 - 30 mai 1985
Frans
kunstcatalogus